PENGEMBANGAN SUPERAPPS PELAYANAN PUBLIK DAN IMPLIKASINYA TERHADAP KEAMANAN DATA SERTA LITERASI DIGITAL ASN - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
The development of public service superapps in Indonesia, such as INA Digital and the Ministry of Law and Human Rights’ Super Apps, promises service efficiency through NIK-based SSO integration in accordance with Presidential Regulation No. 95/2018 on the SPBE. However, the management of large-scale data poses significant cybersecurity risks, including personal data breaches and ransomware attacks, which are regulated by the Personal Data Protection Act No. 27/2022 under the principle of ‘privacy by design’. This literature review analyses civil servants’ digital literacy as a crucial pillar, noting that only 44.9% of civil servants possess good competencies despite the Ministry of Communication and Information Technology’s LDSP programme reaching 80,000 participants. Findings indicate that synergy between data security (zero-trust architecture) and continuous civil servant training is necessary for digital trust and government transformation towards Indonesia Digital 2045.